2020
DOI: 10.1080/02688697.2019.1710825
|View full text |Cite
|
Sign up to set email alerts
|

Rationalising neurosurgical head injury referrals: development and validation of the Liverpool Head Injury Tomography Score (Liverpool HITS) for mild TBI

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our findings elsewhere indicate the majority of patient HCP interactions in CSDH, are by HCP without a specialist interest in CSDH [ 31 ]. For example, most patients present with CSDH at non-specialist hospitals without access to a neurosurgical unit and are referred to a tertiary external neurosurgery unit (NSU) for advice, guidance, and potential transfer [ 10 ]. Not only do they often provide the direct and long-term care, but they will also facilitate shared decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings elsewhere indicate the majority of patient HCP interactions in CSDH, are by HCP without a specialist interest in CSDH [ 31 ]. For example, most patients present with CSDH at non-specialist hospitals without access to a neurosurgical unit and are referred to a tertiary external neurosurgery unit (NSU) for advice, guidance, and potential transfer [ 10 ]. Not only do they often provide the direct and long-term care, but they will also facilitate shared decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited access to neurosurgical expertise in most countries, generalists are expected to care for an expanding volume of both pre-operative, post-operative and non-operative neurosurgical patients; for example, a recent study of traumatic brain injury patients in the UK revealed that only 17% of patients referred to the neurosurgical center were transferred for specialist management. [26][27][28] This can be particularly true in LMICs where neurosurgical provision is scarce. 4,5 Estimates show that the poorest third of the world's population receive only 3•5% of all major surgeries undertaken worldwide.…”
Section: Importance Of Exposure To Neurosurgical Education In Medical Schoolmentioning
confidence: 99%
“…In addition, patients with traumatic brain injury are frequently complicated with hyponatremia, which may trigger neurological dysfunction or even death and disability in severe cases due to damages to the patients' nerve cells. It has been found clinically that the understanding of the causes of traumatic brain injury complicated by hyponatremia serves to a better prognosis of patients and drives down mortality (9)(10)(11). In addition, the clinical treatment of this disease is mainly gastrointestinal sodium supplementation, which has obvious limitations and poor efficacy (12), so it is also urgent to explore more ideal treatment methods.…”
Section: Introductionmentioning
confidence: 99%